Resistance training modes: Specificity and effectiveness - Morrissey, M. C.; Harman, E. A.; Johnson, M. J. (Medicine & Science in Sports & Exercise, 1995)
Research on various types of resistance training and research findings were reviewed. The authors were prepared to offer opinions based on the strength of collective studies. - Isometric versus Concentric Training - Isometric versus Eccentric Training - Isometric versus Concentric/Eccentric (Dynamic) Training - Concentric versus Eccentric Resistance Training - Weight Training versus Isokinetic Exercise - Contraction Velocity - Range of Motion Specificity Implications: This is an excellent review of the research. It tangentially points out that there is not much hard evidence supporting strength training as a viable means for improving athletic (functional) performance. When most studies test on the activities which are trained, and improvements are shown, that may simply be an artifact of a training effect rather than a strength effect. Because arm-curl strength is improved through training does not mean that activities involving the arm will be improved in trained athletes although there may be some improvements in sedentary individuals.